Quality of life related to residual snoring after adenotonsillectomy: a pilot study - Bariani, Rita Catia Brás; Guimaraes, Thais Moura; Moura, Wilana; Cappellette Junior, Mario; Tufik, Sergio; Moreira, Gustavo A.; Fujita, Reginaldo Raimundo (Sleep Science, 2021)
Introduction Few studies have addressed long-term quality of life related to residual snoring after adenotonsillectomy. The aim of this study was to compare scores from the OSA-18 questionnaire between children with residual snoring and non-snoring children two or more years after adenotonsillectomy.Material and Methods The sample comprised 25 children divided into two groups, a group of 14 snoring children, and a control group of 11 non-snoring children. The OSA-18 questionnaire was applied to the volunteers. In the control group, it was completed by the caregivers of the children, while in individuals with residual snoring it was completed by the caregivers of children in the presence of a doctor or dentist. A statistical comparison was made using a generalized linear model.Results The snorer group had a higher total OSA-18 score, and a higher score in all five domains compared to the control group.Conclusion Children with residual snoring two or more years after adenotonsillectomy may have a worse quality of life compared to the control group.
Keywords: Sleep Apnea; Obstructive; Snoring; Indicators of Quality of Life; Tonsillectomy